EFL Higher Vocational Students’ Motivational Regulation and Learner Autonomy in Online Learning Context in China - Yang, Zehua (Journal of Theory and Practice of Social Science, 2023)
Successful online learners must continue to be motivated to learn. The aim of this study was to scrutinize how non-English higher vocational students used learner autonomy and motivational controlling strategies when learning English online. 356 Chinese higher vocational students from a public higher vocational college in the northeast of China served as the study's subjects. A single questionnaire was used to collect information. To control their motivation for online English learning, the participants were discovered to have adopted five different sorts of tactics, however, they used in middle level. Additionally, it was shown that when attending online English lessons, students had a certain amount of learner autonomy. Additionally, in the web-based learning environment, there were significant correlations between students' usage of motivational management tools and their learner autonomy.